The Bible and Politics in Africa - Kügler, Joachim (Bible in Africa studies, 2012)
This volume is based on the International Bible Symposium “The Bible and Politics in Africa” which was held in summer 2010 in Kloster Banz (Germany). The IBS 2010 was organised by Prof. Kügler’s team at the Chair for New Testament Studies at Bamberg University and was generously funded and hosted by the Hanns Seidel Foundation, Munich/ Kloster Banz. Some of the articles published here are based on papers presented at IBS 2010. The editors, however, added some articles to broaden the discussion and to also give a voice to those who could not be present at the symposium. The topic of Biblical influence on politics and of political uses of the Bible is of course not merely an African topic. Christian tradition has always stressed that it not only wants to show ways to heaven but also to reconstruct this world according to God’s will. However the topic seems especially relevant in African societies as many of them ascribe a paramount role to the “Word of God” and thus the Bible seems to be used most directly as a handbook for political actions. With their critical analytical approach the contributors of BiAS 7 try to meet this special challenge for Contextual Biblical Studies which has to be taken more serious than it used to be in academic research.